Level of physical activity in the neighborhoods of the city of São Caetano do Sul, São Paulo, Brazil - Lima, Josivaldo De Souza; Matsudo, Victor Keihan; Ribeiro, Manoel Sampaio (Journal of Health Care, 2016)
The aim of this study was to determine the prevalence of physical activity in the 15 neighborhoods in the cityof São Caetano do Sul (Brazil) in the population above 18 years of age. The sample consisted of 669 subjects,51.9% female with a mean age of 48.1 Â± 17.9, with educational background of 9.0 Â± 4.9 and real income ofBRL 1,341.6 Â± 1,919. The data are from a population survey conducted annually by the Municipal Institutefor Higher Education (IMES) of the Municipal University of São Caetano do Sul and the IMES’ ResearchInstitute (INPES). In household interviews, the short version of the International Physical Activity Questionnaire(IPAQ) was used for data collection, and to determine the level of physical activity we used the consensusbetween the São Caetano do Sul’s Physical Aptitude Laboratory Study Center (CELAFISCS) and theCDC, which classifies physical activity into four categories: "very active", "active", "irregularly active", and"sedentary". In the statistical analysis we used the Kolmogorov-Smirnov test to check the normality of thedata. The ANOVA test was used to verify statistical differences and the Bonferroni test to locate the differenceson the classification of the level of physical activity according to the neighborhoods. The confidence levelwas set at p<0.05. Based on the analyzed data, we concluded that there were no statistically significant differencesbetween the level of physical activity among the studied neighborhoods. However, it was possible toobserve differences among socioeconomic classes and between educational background and level of activity.